Efecto de los micronutrientes en la anemia ferropénica en menores de 5 años que asisten al centro de desarrollo infantil “pequeños brillantes” de Vinces durante el primer semestre del 2018 - Alava Jimenez, Cesar Antonio (2018)
The objective of the research was to evaluate the effect of micronutrients in iron deficiency anemia in children under 5 years of age who attend the "Pequeños Brillantes" Child Development Center of Vinces during the first semester of 2018, since iron deficiency anemia is one of the most frequent nutritional deficiency problems in the early stages of an infant's life. Despite knowing the etiology and its way of prevention at low costs, it still affects this highly vulnerable group, which greatly affect their health. This quasi-experimental study was carried out on 23 children and 17 girls who were subjected to a hematological study with red blood cell count, hematocrit, hemoglobin, erythrocyte levels and serum iron before and after micronutrient supplementation, to assess the efficacy have about anemia and be able to demonstrate the hypothesis that has been embodied in the research project. The results obtained after supplementation were that 67.5% had no anemia, 25% had mild anemia and 7.5% moderate anemia, which represents 13 children with a diagnosis of iron deficiency anemia, with a mean hemoglobin level of 9.5 gr / dl when the accepted normal value for age is 11gr / dl; values in which after fifty days a marked improvement was observed after micronutrient supplementation, now 7.5% have mild anemia and 5% have moderate anemia, with an average hemoglobin of 10.1 g / dl, increasing said value in 0.6 gr / dl. Therefore, it is concluded that the use of micronutritional supplements has a positive effect on iron deficiency anemia when administered appropriately.